2013
DOI: 10.1103/physreva.88.012321
|View full text |Cite
|
Sign up to set email alerts
|

Tree-size complexity of multiqubit states

Abstract: Complexity is often invoked alongside size and mass as a characteristic of macroscopic quantum objects. In 2004, Aaronson introduced the \textit{tree size} (TS) as a computable measure of complexity and studied its basic properties. In this paper, we improve and expand on those initial results. In particular, we give explicit characterizations of a family of states with superpolynomial complexity $n^{\Omega(\log n)}= \mathrm{TS} =O(\sqrt{n}!)$ in the number of qubits $n$; and we show that any matrix-product st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…There are other related compact objects that have been proposed with anisotropic interiors, such as gravastars [6]. Recently, it has also been found that equations of many-body astrophysical systems with spherical symmetry studied in the Post-Newtonian approach resemble those of the above-mentioned anisotropic fluid sources [7]. b) Cosmology: Spacetimes sourced by anisotropic fluids also find application in cosmology.…”
Section: Introductionmentioning
confidence: 98%
“…There are other related compact objects that have been proposed with anisotropic interiors, such as gravastars [6]. Recently, it has also been found that equations of many-body astrophysical systems with spherical symmetry studied in the Post-Newtonian approach resemble those of the above-mentioned anisotropic fluid sources [7]. b) Cosmology: Spacetimes sourced by anisotropic fluids also find application in cosmology.…”
Section: Introductionmentioning
confidence: 98%